2013
DOI: 10.5850/jksct.2013.37.7.894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese Consumers' Ethnocentrism and Animosity on Brand Attitude

Abstract: The Chinese fashion market is a fierce battlefield for foreign brands and domestic brands. This research carefully analyzed several effects based on theories related to the country of origin for brands and consumer attitudes. All data were collected by a questionnaire distributed to Chinese consumers who have experienced global fashion brands. Data collection was conducted in March 2011. A total of 382 complete responses were used for the analysis. The results were as follows: First, for Chinese brands, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…score of -9.697. This finding reinforces prior studies [32] [33] even though they are not researching consumer boycott. Attitude is an affective factor that can be easily influenced by cognitive factors or other affective factors [50], such as anger and resentment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…score of -9.697. This finding reinforces prior studies [32] [33] even though they are not researching consumer boycott. Attitude is an affective factor that can be easily influenced by cognitive factors or other affective factors [50], such as anger and resentment.…”
Section: Discussionsupporting
confidence: 90%
“…This scholar finds a significant impact of animosity on product judgment, boycott participation, and boycott motivation. A Chinese study is conducted by [32]. They investigate the impact of ethnocentrism and animosity on attitude towards Chinese, Japanese, and European fashion brands.…”
Section: Attitude Towards Marketing Communicationmentioning
confidence: 99%
“…In a similar vein, Cui and Choo (2013) found that Chinese consumers' animosity toward Japan results in negative brand sentiments toward Japanese brands. Anger, hostility and unpleasant emotions are produced in Turkish customers by the animosity, which leads to a negative brand attitude toward multinational brands (Barutçu et al, 2016).…”
Section: Consumer Animosity and Brand Attitudementioning
confidence: 84%